Design of the Mobility and Independent Living in Elders Study: An older adult cohort in rural India. Issue 1 (21st December 2015) - Singh, Tushar; Sharma, Pawan K; Jammy, Guru Rajesh; Cauley, Jane A; Bunker, Clareann H; Reddy, PS; Newman, Anne B
Abstract : Aim: The Mobility and Independent Living in Elders Study (MILES) was established in 2012 to estimate the prevalence, incidence, and risk factors for disability and age‐related disease in rural older Indians. Here we describe the main goals of MILES, the essential elements of its design and examinations, and the initial findings from the baseline visit. Methods: A random sample of 562 men and women aged ≥60 years was enrolled from the Medchal region in Telangana State. Baseline examination consisted of two separate clinical visits, and included measurements of blood pressure, anthropometry, physical function, peripheral artery disease, cognitive function, bone and muscle quality, knee osteoarthritis, carotid intima‐media thickness, and blood biomarkers. A comprehensive interview was carried out for demographics, disability and disease history. Annual follow‐up visits are ongoing to collect information on incident disability and disease. Results: The median age of participants was 66 years (range 60–92 years); median body mass index 21.7 kg/m 2, median gait speed 0.67 m/s and 55% self‐reported their health status as fair or poor. Conclusions: These findings suggest a more frail population in the MILES cohort compared with older adults in USA cohorts. MILES will provide estimates of burden of disease, and disability and risk factors in older adults. Findings will be used to identify potential interventions to prevent disability in this rural Indian population.Geriatr Gerontol Int 2017; 17: 31–40.